ANALISIS PRICE BOOK VALUE RATIO SEBAGAI KEPUTUSAN INVESTASI : Penelitian Pada Bursa Efek Jakarta - Idrianita Anis (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
PBV ratio can be used as at tool in fundamental analysis in determining of Investing strategy. Analysis of PBV ratio can help the investor to predict returns of an investment. This research is aimed to explore how PBV ratio relate to stock return, and how PBV ratio relate to fundamental factor of the company. Result of the research find that stocksthat is experienced undervalued will get higher returns and the stocks that is experienced overvalued will get lower retums.This research also analysed the fundamental factors that am predicted to have influence to PBV ratio. They are dividen policy (payout ratio), risk (beta), growth prospect (PAT-growth and EPS-growth) and profitability (ROE). None of these fac-tors that is consistently and significantly has influence to the PBV ratio.The research find that there is negative correlation between PBV ratio and stock return, that is consistent to the research held in many countries.Keywords: PBV ratio, fundamental analysis,investment strategy